The Role of Absence of Close Friends in Suicidal Planning Among Thai Adolescents: Analysis of Nationwide Global School-based Health Survey Data - Ratnawati, Riska; Sham, Shaharuddin Mohd (MEDICA (International Medical Scientific Journal), 2026)
Phenomena of suicide among adolescents in Thailand remains a pressing public health concern. Suicide is the third leading cause of death among adolescents aged 15–19 in Thailand. While previous studies have highlighted psychiatric, familial, and psychosocial risk factors, limited evidence exists on the specific role of peer relationships, particularly the absence of close friends, in suicidal planning. This study objective examined the association between adolescents without close friends and suicidal planning using nationally representative data from the 2021 Global School-based Student Health Survey (GSHS). A cross-sectional design using a secondary data approach was employed, analyzing responses from 4,659 students aged 13–17 years after excluding incomplete cases. The independent variable was the absence of close friends, and the dependent variable was suicidal planning within the past 12 months. Binary logistic regression was conducted, adjusting for confounders including age, sex, loneliness, bullying, parental understanding, and peer kindness. Results indicated that adolescents without close friends had a significantly higher likelihood of reporting suicidal plans (OR = 1.042, 95% CI: 1.026–1.058, p < 0.001). Emotional distress factors such as loneliness and worry-induced sleeplessness, along with experiences of bullying, further amplified risk. These findings align with the Interpersonal Theory of Suicide, which emphasizes thwarted belongingness as a driver of suicidal ideation. The study underscores the protective role of peer relationships in adolescent mental health and highlights the need for interventions that strengthen peer support systems and inclusive school environments. Limitations include reliance on self-reported data and the cross-sectional design, which cannot explains causal inference. Future longitudinal research is recommended to explore temporal ambiguity of peer relationships and suicidality.